ECB and Fed monetary policy measures against the economic effects of the coronavirus pandemic have little effect - Kerstin Bernoth; Geraldine Dany-Knedlik; Anna Gibert (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
To cushion the economic effects of the coronavirus pandemic, central banks havetaken far-reaching monetary policy measures. The US Federal Reserve has loweredits interest rates and, like the European Central Bank, has expanded its bond pur-chase programs. However, it is questionable whether these measures are having thedesired effect of calming the markets and supporting the real economy. It is truethat the macroeconomic effects cannot yet be quantified, but initial indications oftheir effectiveness can be seen in the short-term reactions of stock prices and bondyields. The following article shows how interest rates and prices have reacted direct-ly to the central bank announcements and what conclusions can be drawn from thisfor future measures.
Keywords: 330